Got (the Right) Milk? How a Blended Quality Improvement Approach Catalyzed Change. (October 2015) - Luton, Alexandra; Bondurant, Patricia G.; Campbell, Amy; Conkin, Claudia; Hernandez, Jae; Hurst, Nancy
Abstract : Background: The expression, storage, preparation, fortification, and feeding of breast milk are common ongoing activities in many neonatal intensive care units (NICUs) today. Errors in breast milk administration are a serious issue that should be prevented to preserve the health and well-being of NICU babies and their families. Purpose: This paper describes how a program to improve processes surrounding infant feeding was developed, implemented, and evaluated. Methods: The project team used a blended quality improvement approach that included the Model for Improvement, Lean and Six Sigma methodologies, and principles of High Reliability Organizations to identify and drive short-term, medium-term, and long-term improvement strategies. Findings/Results: Through its blended quality improvement approach, the team strengthened the entire dispensation system for both human milk and formula and outlined a clear vision and plan for further improvements as well. The NICU reduced feeding errors by 83%. Implications for Practice: Be systematic in the quality improvement approach, and apply proven methods to improving processes surrounding infant feeding. Involve expert project managers with nonclinical perspective to guide work in a systematic way and provide unbiased feedback. Create multidisciplinary, cross-departmental teams that include a vast array of stakeholders in NICU feeding processes to ensure comprehensive examination of current state, identification of potential risks, and "outside the box" potential solutions. Implications for Research: As in the realm of pharmacy, the processes involved in preparing feedings for critically ill infants should be carried out via predictable, reliable means including robust automated verification that integrates seamlessly into existing processes. The use of systems employed in pharmacy for medication preparation should be considered in the human milk and formula preparation setting.